Incidence, Risk Factors and Prognosis of T4a Gastric Cancer: A Population-Based Study - Hu, Zhiya; Zuo, Ziyi; Miao, Han; Ning, Zhijie; Deng, Youyuan (Frontiers in Medicine, 2022)
Background: T4a gastric cancer (GC) as a subtype of advanced GC, urgently needs a comprehensive grade method for better treatment strategy choosing. The purpose of this study was to develop two nomograms for predicting the prognosis of T4a GC patients. Methods: A total of 1129 patients diagnosed as T4a GC between 2010 and 2015 were extracted from the Surveillance, Epidemiology, and End Result (SEER) program database. Univariate and multivariate Cox analyses were performed to explore the independent predictors and to establish nomogram for overall survival of the patients, while competing risk analyses was performed to find the independent predictors and to establish nomogram for cancer-specific survival of the patients. The area under the curve (AUC), calibration curve, decision curve analysis (DCA), and Kaplan-Meier analysis were performed to evaluate the nomograms. Results: Older age, larger tumor size, black race, signet ring cell carcinoma, more lymph node involvement, absence of surgery, absence of radiotherapy, and absence of chemotherapy were identified as independent prognostic factors for both overall survival (OS) and cancer-specific survival (CSS). In the training cohort, the AUCs of the OS nomogram were 0.760, 0.743, and 0.723 for 1-, 3- and 5-year OS, while the AUCs of the CSS nomogram were 0.724, 0.703, and 0.713 for 1-, 3- and 5-year CSS, respectively. The calibration curve and DCA indicated that both nomograms can effectively predict OS and CSS, respectively. The above-mentioned results were also confirmed in the validation cohort. Stratification of the patients into high- and low-risk groups highlighted the differences in prognosis between the two groups both in training and validation cohort. Conclusion: Age, tumor size, race, histologic type, N stage, surgery status, radiotherapy, and chemotherapy were confirmed as independent prognostic factors for both OS and CSS in T4a GC patients. Two nomograms based on the above-mentioned variables were constructed to provide more accurate individual survival predictions for them.